Histone octamer dissociation is not required for transcript elongation through arrays of nucleosome cores by phage T7 RNA polymerase in vitro. - O'Neill, T E (1993)
We have examined whether dissociation of the histone octamer is required for elongation of RNA transcripts through arrays of nucleosome cores in vitro. Control or dimethyl suberimidate-crosslinked histone octamers were reconstituted onto supercoiled, closed circular pT207-18 DNA, which contains tandemly repeated 207-base-pair (bp) 5S rDNA nucleosome positioning sequences inserted between the T7 and SP6 transcription promoters of pGEM-3Z. Double label transcription experiments showed that there was little or no effect of extensive crosslinking of the histone octamers on transcription initiation and elongation by T7 RNA polymerase in vitro. Continuous regularly spaced linear arrays of either crosslinked or control nucleosome cores were obtained by digesting reconstituted nucleosomal pT207-18 templates with Dra I, a site that is protected from digestion by the presence of positioned nucleosome cores in the 207-pb sequence. After in vitro transcription with T7 RNA polymerase, an RNA ladder with 207-nucleotide spacing was obtained from templates reconstituted both with crosslinked and with control histone octamers, demonstrating clearly that neither partial nor complete dissociation of the histone octamer is essential for transcription elongation through arrays of nucleosome cores in vitro.